Observation of Backward Guided-Acoustic-Wave Brillouin Scattering in Optical Fibers Using Pump–Probe Technique - Neisei Hayashi; Heeyoung Lee; Yosuke Mizuno; Kentaro Nakamura (IEEE Photonics Journal)
We experimentally demonstrate the observation of backward (i.e., opposite of the direction of the pump) guided-acoustic-wave Brillouin scattering (GAWBS) using the pump–probe technique and investigate the spectral dependence on the pump–probe light power. We show that the signal-to-noise ratio (SNR) of the backward GAWBS measurement can be drastically improved by using this technique. We also observe a nonmonotonic dependence of the SNR on the probe power, which indicates that optimal probe power exists for implementing GAWBS-based distributed sensors.